Prevalence of Spondylolysis in Symptomatic Adolescent Athletes: An Assessment of Sport Risk in Nonelite Athletes. Issue 5 (September 2019) - Selhorst, Mitchell; Fischer, Anastasia; MacDonald, James
Abstract : Objective: To assess the risk of spondylolysis by sport in nonelite adolescent athletes with low back pain (LBP). Design: Retrospective case series. Setting: Hospital-based sports medicine clinic. Patients: The medical charts of 1025 adolescent athletes with LBP (age 15 ± 1.8 years) were examined; 308 (30%) were diagnosed with a spondylolysis. Assessment of Risk: Risk of spondylolysis was assessed in 11 sports for males and 14 sports for females. Main Outcome Measure: Relative risk of diagnosis of spondylolysis injury. Results: The risk of spondylolysis differed by sex with baseball (54%), soccer (48%), and hockey (44%) having the highest prevalence in males and gymnastics (34%), marching band (31%), and softball (30%) for female athletes. Baseball was the only sport to demonstrate a significant increased risk of spondylolysis. Conclusions: The sports with the greatest risk of spondylolysis in adolescent athletes in this study were not consistent with published literature. Clinicians should be cautious generalizing high-risk sports to their practice, as geographic region and level of the athlete may significantly influence the incidence of spondylolysis in the population they are treating.